Determinants Of The Decision To Become An Islamic Bank Customer - Nurul Aisyah; Muhammad Rusdi; Abu Bakar Assidiq (JPS (Jurnal Perbankan Syariah), 2023)
This research investigates the influence of word of mouth, company image, and brand image on customers' decisions to become customers of Islamic banks. This research method is quantitative, using primary data through questionnaires. The research population includes all customers of Bank Sumsel Babel Syariah Palembang Branch. Samples were taken using an accidental sampling technique with 160 respondents. Data analysis was carried out using structural equation modelling using the Partial Least Square method. The research results show that word of mouth, company image, and brand image positively influence the decision to become a customer at an Islamic bank. The results of this research can complement existing theories and be a reference in developing Islamic banking policies, improving services, and customer interest in Islamic banks. In addition, the results of this research also provide valuable insights for future scientific research.